Dissecting Hafalan Shalat Delisa Movie (Character Education Values embedded in the movie for elementary school students) - Sulthoniyah, Luluk; Muhith, Abd (Attadib: Journal of Elementary Education, 2024)
This study is a part of a literature review that attempts to identify the character education principles that are taught to primary school pupils in the movie Hafalan Salah Delisa. This study focuses on the application of character education. To gather data, it consults library materials and the movie Hafalan Shalat Delisa. Library materials provide information about character education, while movie shows provide information about the values the movie portrays. Our research has led us to the conclusion that the movie Hafalan Shalat Delisa contains character education values. These values include religious principles, honesty, tolerance, discipline, hard work, creativity, and independence; they also include a high degree of curiosity; respect for success and achievement; love and love; a love of reading; care for the environment; care for social issues; and responsibility. The film's morals are applied in compliance with Minister of Education and Culture Regulation number 20 of 2018, which aims to improve character educationKeyword: Character Eduction Values, Hafalan Shalat Delisa.